A study on schemes of State Bank of India for lending to MSMEs - Rashmi Sarda; Dr. Devi Baruah (International Journal of Management Studies (IJMS), 2021)
Rightly said to be backbone of any economy, MSMEs promote equitable development and overall societal welfare and stability by creating additional job opportunities. Access to finance is widely believed to be the most important challenge faced by MSMEs worldwide. State Bank of India has been playing a critical role in the overall growth and development MSMEs through various schemes. Thus, the present paper attempts to study the lending practice of SBI in Jorhat district of Assam under various schemes.